2017
DOI: 10.1534/g3.117.300227
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin Ligase (E3) Psh1p Is Required for Proper Segregation of both Centromeric and Two-Micron Plasmids in Saccharomyces cerevisiae

Abstract: Protein degradation by the ubiquitin-proteasome system is essential to many processes. We sought to assess its involvement in the turnover of mitochondrial proteins in Saccharomyces cerevisiae. We find that deletion of a specific ubiquitin ligase (E3), Psh1p, increases the abundance of a temperature-sensitive mitochondrial protein, mia40-4pHA, when it is expressed from a centromeric plasmid. Deletion of Psh1p unexpectedly elevates the levels of other proteins expressed from centromeric plasmids. Loss of Psh1p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…We did not observe a significant difference in plasmid retention for hir2D (65%) when compared to the psh1D hir2D (58%) strain (Figure 7G). Previous studies have also reported plasmid retention defects in a psh1D strain (Herrero and Thorpe 2016;Metzger et al 2017). Taken together, our results show that Hir2 facilitates the interaction of Cse4 with Psh1, and this may contribute to the increased plasmid loss in hir2D strains.…”
Section: Hir2 Interacts With Cse4 and Facilitates The Interaction Of Cse4 With Psh1 To Promote Cse4 Proteolysissupporting
confidence: 82%
“…We did not observe a significant difference in plasmid retention for hir2D (65%) when compared to the psh1D hir2D (58%) strain (Figure 7G). Previous studies have also reported plasmid retention defects in a psh1D strain (Herrero and Thorpe 2016;Metzger et al 2017). Taken together, our results show that Hir2 facilitates the interaction of Cse4 with Psh1, and this may contribute to the increased plasmid loss in hir2D strains.…”
Section: Hir2 Interacts With Cse4 and Facilitates The Interaction Of Cse4 With Psh1 To Promote Cse4 Proteolysissupporting
confidence: 82%
“…Similarly to these studies, we show that a number of plasmid copies may increase in selective conditions and confer adaptation to mutations in release factor genes ( Figure 2 ). In one of the recent works, it has been shown that the PSH1 gene controls plasmid segregation and copy number [ 43 ]. Hence, it may be hypothesized that the activity of this gene contributes to the phenomenon of adaptation investigated in our work.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of PSH1 or CKA2 , one of the two catalytic subunits of CK2, resulted in poor growth when Cse4 was overexpressed and higher levels of Cse4 incorporation at non-centromeric sites ( 10–12 ). Deletion of PSH1 with overexpression of Cse4 could potentially affect kinetochore function, and consistently, Psh1 may contribute to plasmid segregation ( 45 ), but this does not seem to fully explain the growth defect ( 11 , 46 ). If part of the growth defect is due to disruption of chromatin-based processes from misincorporation of Cse4, and CAF-1 is responsible for targeting Cse4 into ectopic chromosome regions, then deletion of CAF-1 subunits might rescue the slow growth observed upon Cse4 overexpression in psh1Δ and cka2Δ strains.…”
Section: Resultsmentioning
confidence: 99%